Connecting worlds (Journal of Parents and Teachers, 2014)
“Connecting worlds” is a virtual forum opened by Intermón Oxfam's. it is an educational program, which proposes a series of virtual activities whose purpose is to share experiences of work and study among students, as well as knowledge and research on social and cultural issues. With this, it is intended to make a list of problems to present to the political leaders.
Keywords: Connecting worlds; virtual forum; social problems; social initiative.